A fusion of research-informed teaching and teaching-informed research : Designing a scalable online ecosystem for new partnerships in educational research. - Egan, Alison; Connolly, Cornelia; Hall, Tony; Ryan, Marie; McMahon, Jennifer; McGann, Marek (Australasian Society for Computers in Learning in Tertiary Education, 2021)
This paper examines the unbundling of research in the context of the Teachers’ Research Exchange (T-REX) platform, the national flagship Internet platform in Ireland for teachers to access, use and engage in research. This paper draws on two theoretical frameworks: Laurillard’s conversational framework and Salmon’s five-stage model. The first highlights the experimental, exploratory and creative aspects of developing an overall framework to structure the digital learning environment for teachers-as-researchers. The second explores the future of higher education and systems like T-REX in the era of digital transformation and the emerging context of Education 4.0. The original contribution is the integration of these frameworks in the creation of an open and shared learning platform so that schools and teachers can be supported to access, collaborate in and undertake research. In particular, the paper outlines signature features of the T-REX design and the way it has emerged over the last 5 years as an innovative platform to mediate the fusion of research and teaching in education. The paper highlights key issues and challenges in unbundling the traditional university, particularly in the context of educational research, but also the imperative of doing so, in the emerging era of Education 4.0. Implications for practice or policy: Supporting teachers’ research engagement is increasingly identified as a key priority in the improvement of educational standards and systems. T-REX is of value to educationalists interested in a shared learning and open online teacher-research platform. There should be a dialogic approach to the relationship between teaching and research, where each informs and enhances the other.
Keywords: Education 4.0; Online Research Community; Digital Learning; Digital Transformation; Higher Education; Teacher Research